Risk Factors For Dyslipidemia In Urban Elderly - Lely Wahyuniar (Jurnal Medisci, 2026)
Background. Dyslipidemia is one of the primary health issues among urban elderly individuals that can increase the risk of cardiovascular disease. Dyslipidemia occurs due to an imbalance in lipids such as cholesterol, low-density lipoprotein (LDL-C), triglycerides, and high-density lipoprotein ( HDL). Several risk factors that can increase lipid levels include age, gender, education, occupation, diet, physical activity, and smoking habits. Aims. Research objective: To analyze the relationship between age, gender, education, occupation, diet, physical activity, and smoking habits with the incidence of dyslipidemia in elderly people in RW 04, Kel.Grogol Utara, Kec. Kebayoran Lama, South Jakarta, DKI Jakarta Province. Methods. The research method used a quantitative, cross-sectional design. Data collection was conducted from July to October 2025, involving 147 respondents. Result. The results showed that there was no significant relationship between age (p=0.25), gender (p=0.72), education (p=0.116), occupation (p=0.57), diet (p=0.294), and smoking habits (p=0.48) with the incidence of dyslipidemia in the elderly. Only physical activity had a significant relationship (p=0.0006) with the incidence of dyslipidemia in the elderly in RW 04, Kel.Grogol Utara, Kec. Kebayoran Lama, South Jakarta, DKI Jakarta Province. Conclusion. There is a need for a multidisciplinary approach and innovative interventions, such as strengthening educational interventions, organizing community or virtual exercise classes that can be accessed from home, and utilizing digital technology, such as telemedicine platforms and health applications (e-health), to facilitate remote monitoring.